Relativistic Fluid Dynamics Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Bressanone (Bolzano), Italy, June 7-16, 1970 - Cattaneo, C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Pham Mau Quam: Problèmes mathématiques en hydrodynamique relativiste.- A. Lichnerowicz: Ondes de choc, ondes infinitésimales et rayons en hydrodynamique et magnétohydrodynamique relativistes.- A.H. Taub: Variational principles in general relativity.- J. Ehlers: General relativistic kinetic theory of gases.- K. Marathe: Abstract Minkowski spaces as fibre bundles.- G. Boillat: Sur la propagation de la chaleur en relativité.
Pham Mau Quam: Problèmes mathématiques en hydrodynamique relativiste -- A. Lichnerowicz: Ondes de choc, ondes infinitésimales et rayons en hydrodynamique et magnétohydrodynamique relativistes -- A.H. Taub: Variational principles in general relativity -- J. Ehlers: General relativistic kinetic theory of gases -- K. Marathe: Abstract Minkowski spaces as fibre bundles -- G. Boillat: Sur la propagation de la chaleur en relativité.
Keywords: Partial differential equations; Mechanics; Mechanics, Applied; Gravitation; Partial Differential Equations; Solid Mechanics; Classical and Quantum Gravitation, Relativity Theory